2005
DOI: 10.1017/s0272263105050035
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Second Language Sentence Processing

Abstract: Four groups of second language (L2) learners of English from different language backgrounds (Chinese, Japanese, German & Greek) and a group of native speaker controls participated in an on-line reading-time experiment with sentences involving long-distance wh-dependencies. While the native speakers showed evidence of making use of intermediate syntactic gaps during processing, the L2 learners appeared to associate the fronted wh-phrase directly with its lexical subcategoriser, regardless of whether or not the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
275
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(295 citation statements)
references
References 33 publications
17
275
3
Order By: Relevance
“…The results from Marinis et al (2005) revealed that, whereas the native speakers showed clear evidence for facilitation at the final gap when an intermediate gap was present, none of the L2 groups revealed a similar pattern, or indeed any differences for processing (1) vs. (2). Since their comprehension of the sentences was not affected, Marinis et al concluded that L2 learners process long-distance dependencies successfully, albeit not relying on abstract syntactic cues but on lexical, thematic and pragmatic information.…”
Section: Processing Of Syntactic Dependencies By Non-native Speakersmentioning
confidence: 88%
See 2 more Smart Citations
“…The results from Marinis et al (2005) revealed that, whereas the native speakers showed clear evidence for facilitation at the final gap when an intermediate gap was present, none of the L2 groups revealed a similar pattern, or indeed any differences for processing (1) vs. (2). Since their comprehension of the sentences was not affected, Marinis et al concluded that L2 learners process long-distance dependencies successfully, albeit not relying on abstract syntactic cues but on lexical, thematic and pragmatic information.…”
Section: Processing Of Syntactic Dependencies By Non-native Speakersmentioning
confidence: 88%
“…sentences with long-distance syntactic dependencies, it is not fully understood whether comprehension is achieved via processing of the abtract syntactic structure of a sentence, as the expectation is for native processing, or via heuristic information, such as lexical and semantic cues (Dallas & Kaan 2008). One of the first studies attempting to directly tease apart syntactic from lexical-semantic processing in L2 was conducted by Marinis et al (2005). Marinis and colleagues tested a group of native speakers of English and four groups of non-native speakers in a self-paced reading (SPR) task with sentences such as the following:…”
Section: Processing Of Syntactic Dependencies By Non-native Speakersmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to answer this question, researchers have focused largely on identifying and accounting for the similarities and differences between first-language (L1) and L2 sentence processing. Although there appears to be considerable overlap in the characteristics of L1 and L2 sentence comprehension, salient L1/L2 processing differences include disparities in global performance (i.e., generally slower and less accurate performance in the L2; among others, see Cook, 1997;Frenck-Mestre, 2002;Hahne & Friederici, 2001), as well as differential sensitivity to certain morphosyntactic cues (Guillelmon & Grosjean, 2001;Jiang, 2004Jiang, , 2007Liu & Nicol, 2010;MacWhinney, 2002) and syntactic information (Marinis, Roberts, Felser, & Clahsen, 2005). These and other differences have been explained in terms of deficient L2 competence, even for highly proficient L2 users (Clahsen & Felser, 2006a;Jiang, 2004Jiang, , 2007; but see Clahsen & Felser, 2006b), as well as in terms of differences between the L1 and L2 processing systems.…”
mentioning
confidence: 99%
“…For example, their performance in resolving relative clause attachment ambiguities was random even in situations where L1 and L2 are similar (Felser et al 2003). In resolving long-distance filler-gap dependencies, they were shown to have failed to reactivate the structural gap (Marinis et al 2005). The conclusion in Clahsen and Felser (2006) was that though L2 learners are guided by lexical-semantic cues during sentence parsing in the same way as native speakers, they are less able to make use of (complex) syntactic information.…”
Section: Sensitivity To Morphosyntax and Role Of Inputmentioning
confidence: 99%